2010
DOI: 10.1021/jo1012509
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Kinetic Analysis of Carbon−Carbon Bond Fragmentation Reactions of Cation Radicals Derived from SET-Oxidation of Lignin Model Compounds

Abstract: Features of the oxidative cleavage reactions of diastereomers of dimeric lignin model compounds, which are models of the major types of structural units found in the lignin backbone, were examined. Cation radicals of these substances were generated by using SET-sensitized photochemical and Ce(IV) and lignin peroxidase promoted oxidative processes, and the nature and kinetics of their C-C bond cleavage reactions were determined. The results show that significant differences exist between the rates of cation rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 113 publications
7
87
1
Order By: Relevance
“…The coupling was also possible with thiophenes and N-Boc-pyrrole, albeit in lower yields. The proposed mechanism (Scheme 156) is consistent with redox potential data, which indicate that [EY]* should be able to reduce diazonium 156.1, and the aryl radical 156.4 generated by loss of N 2 adds to the heteroarene at the 2-position to give the resonance-stabilized radical 156 498 The aryl radical intermediate is thought to be captured by the alkyne, and cyclohexadienyl radical 157.10 is formed after a subsequent radical cyclization. Turnover of the PET cycle may occur by reduction of EYH 2 • + by cyclohexadienyl radical; however, a chain propagating electron transfer to the diazonium starting material may be possible.…”
Section: Chemical Reviewssupporting
confidence: 63%
“…The coupling was also possible with thiophenes and N-Boc-pyrrole, albeit in lower yields. The proposed mechanism (Scheme 156) is consistent with redox potential data, which indicate that [EY]* should be able to reduce diazonium 156.1, and the aryl radical 156.4 generated by loss of N 2 adds to the heteroarene at the 2-position to give the resonance-stabilized radical 156 498 The aryl radical intermediate is thought to be captured by the alkyne, and cyclohexadienyl radical 157.10 is formed after a subsequent radical cyclization. Turnover of the PET cycle may occur by reduction of EYH 2 • + by cyclohexadienyl radical; however, a chain propagating electron transfer to the diazonium starting material may be possible.…”
Section: Chemical Reviewssupporting
confidence: 63%
“…LCC linkages comparing hydrogen and covalent bonds in cellulose-hemicellulose and lignin-hemicellulose complexes were assessed using DFT calculations [219].The authors concluded that the ether bonds in LCCs were less stable in pretreatment, though a more comprehensive understanding of the nature of bonding between sugars and lignin covering different categories will be necessary for targeting these linkages. DFT calculations on lignin model compounds not only were successful in predicting the BDEs and reactivity trend on experimentally observed product selectivities but also emphasized the roles of electron delocalization and methoxy group effects on the radical cation formation [220]. Also, the dissociating linkages can have different adjacent substituents, such as the methoxy functionality on arene rings and hydrocarbon, methyl, and hydroxyl group substitutions on aliphatic carbon atoms.…”
Section: Computational Aspects Of Lignin Linkagesmentioning
confidence: 99%
“…Among the three peroxidase families LiP, first reported from Phanerochaete chrysosporium [15], and VP, described later from Pleurotus eryngii [16, 17], have attracted the highest interest since they are able to degrade nonphenolic model compounds representing the main substructures in lignin (such as β- O -4′ alkyl-aryl ethers) [1820] by single-electron abstraction forming an aromatic cation radical [21], and subsequent C α –C β bond cleavage [22] (while MnP would act on the minor phenolic units). From the discovery of LiP, the huge number of biochemical and molecular biology studies on these enzymes generally used simple aromatic substrates, such as veratryl (3,4-dimethoxybenzyl) alcohol [2325], and similar studies using the real lignin substrate are extremely rare [26].…”
Section: Introductionmentioning
confidence: 99%